[Translated Technical Note] Emergency managers’ perceptions of Early Warning Systems (EWS) products and probabilistic information - Stoll Villarreal, Luciana (2023)
Fil: Stoll Villarreal, Luciana. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias de la Atmosfera y los Océanos;Argentina.